2023
DOI: 10.29374/2527-2179.bjvm000323
|View full text |Cite
|
Sign up to set email alerts
|

Dental and oral cavity alterations in Quarter Horses of Vaquejada: retrospective study of 416 cases (2012 2022)

Abstract: Oral and dental diseases are common in horses, as evidenced by the results of incidence studies of dental diseases carried out on abattoir specimens or sports horses. Thus, periodic dental examinations in horses are essential to ensure the maintenance of dental health and proper use of ingested food. A retrospective study of the dental records of 416 Quarter Horses (256 males, 160 females), distributed in the western region of the Rio Grande do Norte, Brazil, was conducted. Horses were examined between July 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…The data obtained through this study make it possible to show that the majority of the interviewed horse owners adopted a semi-intensive breeding regime, and a smaller proportion adopted intensive and extensive regimes. These results are similar to those obtained by Melo and Ferreira (2023) in a retrospective study on dental alterations in vaquejada horses, where athletic horses were kept most of the day in stalls with restricted access to paddocks during the night. A similar observation was made by Dias et al (2013) in a cross-sectional study that showed that 53.6% of the horses used in vaquejada were bred in a semi-intensive regime with access to paddocks and remained in the stall for over 11 hours a day.…”
Section: Discussionsupporting
confidence: 88%
“…The data obtained through this study make it possible to show that the majority of the interviewed horse owners adopted a semi-intensive breeding regime, and a smaller proportion adopted intensive and extensive regimes. These results are similar to those obtained by Melo and Ferreira (2023) in a retrospective study on dental alterations in vaquejada horses, where athletic horses were kept most of the day in stalls with restricted access to paddocks during the night. A similar observation was made by Dias et al (2013) in a cross-sectional study that showed that 53.6% of the horses used in vaquejada were bred in a semi-intensive regime with access to paddocks and remained in the stall for over 11 hours a day.…”
Section: Discussionsupporting
confidence: 88%
“…Excessive enamel tips occur mainly because of changes in the eating habits of horses (PAGLIOSA et al, 2006). Enamel tips are the most reported alterations in equine dentistry, with a reported incidence between 44% and 85.1% (BERBARI NETO et al, 2013;LEITE et al, 2019;MELO;FERREIRA, 2023), being more prevalent in horses up to 9 years of age because of the rhizogenesis of permanent teeth (PAGLIOSA et al, 2006). The introduction of concentrated feeds and the reduction in forage supply decrease chewing time and promote more vertical chewing movements, which result in changes in tooth wear.…”
Section: Resultsmentioning
confidence: 99%
“…Dental overgrowth restricts anterior/posterior and lateral movements of the jaw (DIXON; DACRE, 2005;EASLEY et al, 2016). Recently, Melo & Ferreira (2023) observed a high correction between the enamel tips and limited and asymmetrical mandibular lateral excursion. The presence of enamel tips may justify the limited mandibular excursion in some of the study population; however, Dixon & Dacre (2005) contended that hooks or ramps can also result in impaired jaw movement.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation